POGIL (process oriented guided inquiry learning) learning model: How does it influence students' observation skills and scientific attitudes? - Fira Fitria; Nur Hidayah (CV. FOUNDAE, 2021)
Poor observation skills and scientific attitudes are important factors to note. One of the external factors affecting the problems is the lack of innovative learning models used by teachers. The Process Oriented Guided Inquiry Learning (POGIL) learning model is one of the models that can be used to solve this problem. This research aimed to determine whether the POGIL learning model affects students' observation skills, scientific attitudes, and observation skills and scientific attitudes. The research method used was quasi-experimental with a posttest-only control group design. The research subjects were determined through cluster random sampling technique. The research instruments used were observation sheets and scientific attitudes questionnaires. The obtained data were analyzed using parametric statistics of Multivariate Analysis of Variance (MANOVA). The results showed that the POGIL learning model presented positive effects on 1) students' observation skills, 2) students' scientific attitudes, and 3) students' observation skills and scientific attitudes.